Role of osteogenic growth peptide (OGP) and OGP(10–14) in bone regeneration: A review - Pigossi, Suzane C. [UNESP]; Medeiros, Marcell C. [UNESP]; Saska, Sybele [UNESP]; Cirelli, Joni A. [UNESP]; Scarel-Caminaga, Raquel M. [UNESP] (MDPI, 2016)
Bone regeneration is a process that involves several molecular mediators, such as growth factors, which directly affect the proliferation, migration and differentiation of bone-related cells. The osteogenic growth peptide (OGP) and its C-terminal pentapeptide OGP(10–14) have been shown to stimulate the proliferation, differentiation, alkaline phosphatase activity and matrix mineralization of osteoblastic lineage cells. However, the exact molecular mechanisms that promote osteoblastic proliferation and differentiation are not completely understood. This review presents the main chemical characteristics of OGP and/or OGP(10–14), and also discusses the potential molecular pathways induced by these growth factors to promote proliferation and differentiation of osteoblasts. Furthermore, since these peptides have been extensively investigated for bone tissue engineering, the clinical applications of these peptides for bone regeneration are discussed.
Keywords: Biocompatible materials; Bone regeneration; Osteoblasts; Osteogenic growth peptide